ANALYSIS OF WORK NETWORK FRAME RELAY TECHNOLOGY AT PT. CITRA SARI RECEIPTS - Sigit Riyanto; Sutarno Sutarno, SKom., MMSi. (Jurnal Sistem Informasi, 2008)
In scientific writing, the author tries to analyze the work of one of the datacommunication networking technology that is popular Frame Relay technology. Ofthe several kinds of existing data technologies such as Leased Line, X.25, ATM,MPLS and many others, Frame Relay is a network technology that is widely usedtoday because they have various advantages.To be able to use the Frame Relay network needed a reliable network infrastructure,from the LAN (Local Area Network) and also a WAN network (Wide AreaNetwork). Frame relay itself is a technology that works within the WAN network,and the main function of frame relay is to deliver data from one point (source) toanother point (goal) with the media through the network (kabel. Radiolink orsatellite).For that, as the data supporting the authors also observed in PT. Citra Sari Makmurwhich is a network service provider (service provider) operating in frame relaynetworks, especially networks.